Earning per Share, Debt to Equity Ratio and Return on Equity in Stock Prices - Wiyana, Jessica Dewi; Dewi, Nurma Gupita (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Investment is an important element that contributes to business expansion and progress. This study aims to examine how earnings per share, debt-to-equity ratio, and return on equity affect the stock prices of pharmaceutical companies on the IDX from 2018 to 2020. The focus is on pharmaceutical companies listed on the IDX from 2018 to 2022. The results reveal that while ROE has a positive effect on prices, its impact is minimal compared to EPS and DER, which both have a positive effect. The inference test showed an adjusted R-squared value of 0.211. This means that only 21.1% of the changes in stock prices can be explained by the independent variables EPS, DER, and ROE. Additional elements not included in this research affected the remaining 78.9%.